Product Quality of Upcycle Denim Jacket Fashion with Slashing Fabric Manipulation Technique - Sabrina Ratu Mawaddah; Esty Nurbaity Arrsyi; Sri Listiani (Journal of Creative Industries and Vocational Innovation, 2025)
This research aims to obtain a product assessment of the utilization of accumulated clothing, especially unused second hand denim jackets, in the process of making upcycled denim jackets. The approach used in this research is the descriptive quantitative method with a pre-experimental research design, in the form of a one shot case study. This research produced five ready-to-wear fashion products in the form of upcycled denim jackets decorated with fern motifs as the main theme, applied through the slashing fabric manipulation technique, and assessed using a rating scale. The research stages included the accumulation of second hand denim jackets, processing, and making upcycled denim jackets. Product assessment of upcycled second hand denim jackets with slashing technique fabric manipulation is based on the theory of Product Quality according to David Garvin in Fandy Tjiptono, which includes features, reliability, suitability, and aesthetics. The assessment results show that the overall product quality is in the very good category. Products with a very high category were obtained by design 1 obtained a very good score. meanwhile, designs 4 and 5 obtained good scores.